A photoelectrochemical aptasensor based on double Z-scheme α-Fe2O3/MoS2/Bi2S3 ternary heterojunction for sensitive detection of circulating tumor cells - Feng, Kai; Di, Ya; Han, Meng; Yan, Weitao; Guo, Yulin; Huai, Xiangqian; Wang, Yimin (Frontiers in Bioengineering and Biotechnology, 2024)
A novel photoelectrochemical (PEC) aptasensor based on a direct dual Z-scheme α-Fe2O3/MoS2/Bi2S3 ternary heterojunction for the ultrasensitive detection of circulating tumor cells (CTCs) was developed. The α-Fe2O3/MoS2/Bi2S3 nanocomposite was prepared via a step-by-step route and photoproduced electron/hole transfer path was speculated by trapping experiments of reactive species. α-Fe2O3/MoS2/Bi2S3-modified electrodes exhibited greatly enhanced photocurrent under visible light due to the double Z-scheme charge transfer process, which met the requirement of PEC sensor for detecting larger target. After the aptamer was conjugated on the photoelectrode through chitosan (CS) and glutaraldehyde (GA), when MCF-7 cells were presented and captured, the photocurrent of PEC biosensing system decreased due to steric hindrance. The current intensity was linear relationship with the logarithm of MCF-7 cells concentration in the range from 10 to 1×10 5 , with a low detection limit of 3 cell mL -1 (S/N=3). The dual Z-scheme α-Fe2O3/MoS2/Bi2S3 ternary heterojunction -modified PEC aptasensor exhibited high sensitivity and excellent specificity, and stability. Additionally, MCF-7 cells in human serum was determined by this PEC aptasensor, exhibiting great potential as a promising tool for clinical detection.